INTEGRASI ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Nadya Azzahra; Asep tutun Usman; Anton (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the literature of published journals regarding the use of Artificial Intelligence (AI) or better known as artificial intelligence used in Islamic Religious Education learning. The study uses a Systematic Literature Review approach with the stages of theme determination, search, literature selection, analysis and interpretation, drafting, and dissemination of results. In the study conducted using 15 articles from a selection of 30 articles obtained from various sources with the years of publication 2020-2024. The results of the study indicate that: 1) The use of AI in Islamic Religious Education learning uses various platforms such as visual mentors, Voice Assistants such as Google Assistant, Siri, and Cortana and Presentation Translators and so on. 2) The implications of the use of AI in Islamic Religious Education learning have positive and negative impacts so that evaluation is needed. 3) The use of AI faces many challenges such as the risk of causing distortion and misinterpretation of religious texts, as well as the emergence of an attitude of dependence on technology, the potential influence of foreign cultures, data insecurity, and the risk of reduced human interaction.Keywords: Artificial Intelligence, Learning, Islamic Religious Education